Increasing temporal stability of global tropical cyclone precipitation - E Deng; Qian Xiang; Johnny C. L. Chan; Yue Dong; Shifei Tu; Pak-Wai Chan; Yi-Qing Ni (npj Climate and Atmospheric Science)
Abstract Tropical cyclone (TC) precipitation has led to escalating urban flooding and transportation disruptions in recent years. The volatility of the TC rain rate (RR) over short periods complicates accurate forecasting. Here, we use satellite-based observational rainfall datasets from 1998 to 2019 to calculate changes in TC 24-h RR and quantify the temporal stability of TC precipitation. We demonstrate a significant global increase in the annual temporal stability of TC RR across the total rainfall area, inner-core, and rainband areas. Specifically, the probabilities of rapid RR increase and decrease events in the TC total rainfall area decreased at rates of –1.74 ± 0.57% per decade and –2.23 ± 0.55% per decade, respectively. Based on the reanalysis dataset, we propose that the synergistic effects of increased atmospheric stability and total column water vapor—both resulting from anthropogenic warming at low latitudes—are potentially associated with this trend.